HUBUNGAN STRES AKADEMIK DENGAN BURNOUT SCHOOL DAN EMOTIONAL EATING PADA REMAJA SISWA KELAS XII SMA NEGERI 1 MOJOLABAN - Agil Siradj; Mental Health; Ady Irawan AM (Institut Kesehatan Pelamonia, 2026)
Adolescents, particularly twelfth-grade senior high school students, are vulnerable to academic stress due to increasing academic demands, assignment completion, examination preparation, and planning for higher education and future careers after graduation. Prolonged academic stress may contribute to the development of *school burnout* and changes in eating behavior, such as *emotional eating. Objective: To analyze the relationship between academic stress and school burnout as well as emotional eating among twelfth-grade students at SMA Negeri 1 Mojolaban. Methods: This study employed a quantitative approach using a cross-sectional correlational design. A total of 64 twelfth-grade science students were selected through proportionate stratified random sampling. Data were collected using the *Educational Stress Scale for Adolescents (ESSA), the **School Burnout Inventory (SBI), and the **Dutch Eating Behavior Questionnaire (DEBQ). Data were analyzed using descriptive statistics, Spearman's rho correlation test, and ordinal logistic regression. Results: Most respondents experienced moderate levels of academic stress (78.1%), school burnout (50.0%), and emotional eating (48.4%). A statistically significant positive correlation of moderate strength was found between academic stress and school burnout (r = 0.466; p = 0.001), whereas no significant relationship was found between academic stress and emotional eating (p = 0.247). Ordinal logistic regression analysis indicated that academic stress was a significant predictor of school burnout, explaining 23.8% of its variance. Findings: Increased academic stress contributed to a higher risk of school burnout but was not directly associated with emotional eating. Implications: These findings highlight the importance of the collaborative roles of nurses, teachers, and schools in developing mental health promotion programs, early identification of academic stress, and stress management interventions to prevent school burnout and promote adolescents' psychological well-being in the school setting.